Modelling the time at which overcrowding and feed interruption emerge on the swine premises under movement restrictions during a classical swine fever outbreak. (2nd August 2016) - Weng, H. Y.; Yadav, S.; Olynk Widmar, N. J.; Croney, C.; Ash, M.; Cooper, M.
Abstract : A stochastic risk model was developed to estimate the time elapsed before overcrowding (TOC) or feed interruption (TFI) emerged on the swine premises under movement restrictions during a classical swine fever (CSF) outbreak in Indiana, USA. Nursery (19 to 65 days of age) and grow-to-finish (40 to 165 days of age) pork production operations were modelled separately. Overcrowding was defined as the total weight of pigs on premises exceeding 100% to 115% of the maximum capacity of the premises, which was computed as the total weight of the pigs at harvest/transition age. Algorithms were developed to estimate age-specific weight of the pigs on premises and to compare the daily total weight of the pigs with the threshold weight defining overcrowding to flag the time when the total weight exceeded the threshold (i.e. when overcrowding occurred). To estimate TFI, an algorithm was constructed to model a swine producer's decision to discontinue feed supply by incorporating the assumptions that a longer estimated epidemic duration, a longer time interval between the age of pigs at the onset of the outbreak and the harvest/transition age, or a longer progression of an ongoing outbreak would increase the probability of a producer's decision to discontinue the feed supply. Adverse animal welfare conditions were modelled to emerge shortly after an interruption of feed supply. Simulations were run with 100 000 iterations each for a 365-day period. Overcrowding occurred in all simulated iterations, and feed interruption occurred in 30% of the iterations. The median (5th and 95th percentiles) TOC was 24 days (10, 43) in nursery operations and 78 days (26, 134) in grow-to-finish operations. Most feed interruptions, if they emerged, occurred within 15 days of an outbreak. The median (5th and 95th percentiles) time at which either overcrowding or feed interruption emerged was 19 days (4, 42) in nursery and 57 days (4, 130) in grow-to-finish operations. The study findings suggest that overcrowding and feed interruption could emerge early during a CSF outbreak among swine premises under movement restrictions. The outputs derived from the risk model could be used to estimate and evaluate associated mitigation strategies for alleviating adverse animal welfare conditions resulting from movement restrictions.